(untitled) (Medico Legal Update, 2020)
Objectives: The study aims at evaluating the nurses’ evidence-based practices at primary health care centers in Baghdad City. Methodology: A descriptive design is carried out at Baghdad City’s primary health care centers from January 2en 2019 to June 1st 2020. One instrument is developed for the purpose of the study. A Non-probability, multi stage purposive sample of (52) staff nurses, who are working at primary health care centers in Baghdad City. The instrument is concerned with the evaluation of nurses’ evidence-based practices through (43) items which are divided in to five main domains of attitudes, knowledge, beliefs, readiness and applications of evidence-based practices. Content validity of the questionnaire is determined by panel of (10) experts and Internal consistency reliability, Split-half technique, is obtained through Cronbach alpha correlation coefficient. Data are collected through the use of the study instrument and the interview technique as means of data collection. Data are analyzed through the use of descriptive statistical data analysis approach of frequencies, percentages, total scores and ranges. Results: The study findings indicate that the majority of the staff nurses have experienced poor level of knowledge, attitudes, beliefs, readiness and application as dimensions of nurses’ evidence-based practices. Conclusion: The study findings depict that staff nurses have experienced inadequate evidence-based practices at primary health care centers. Recommendation: Planned training sessions can be designed, constructed and implemented to staff nurses at the primary health care centers relative to evidence-based practices.